Upon the Walls of the UN Camp: Situated Intersectionality, Trajectories of Belonging, and Built Environment Among Syrian Refugees in the Kurdistan Region of Iraq. (1st January 2018) - Hayes, Jordan Clarke
Abstract : Upon the walls of homes in the Arbat 'camp' community in the Kurdistan Region of Iraq (KRI), the ubiquitous UN logo lays claim to a built environment disrupted by ornamental facades, muralism, and radical iconography. Engaging photographs and qualitative interviews gathered in the Kurdish Region of Iraq in 2017 and 2018, this essay traces expressions of "belonging" within a situated intersectional framework to surface and assess the categories of social division evident in Arbat's non-Western context.